IDEOLOGICAL CONSTRUCTION FOUND IN THE POLITICAL CAMPAIGN ADVERTISEMENT OF PDIP BROADCASTED BY METRO TV - KINASIH, SALSABILA SASMI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Critical Discourse Analysis, Advertisement, PDIP Critical Discourse Analysis (CDA) is one of linguistics branches which concerns with the correlation between language and power and ideology. Linguistic practices, in this case advertisement, have the power to spread and shape ideologies towards the society. The aim of this research is to reveal the constructed ideology behind the political campaign advertisement of Partai Demokrasi Indonesia Perjuangan (PDIP) broadcasted by a local TV channel, Metro TV, during the campaign period of president election in 2014. This research uses Fairclough’s Model of CDA. It consists of three stages; description, interpretation and explanation. The first stage deals with the linguistic features of the texts, the second stage deals with the process of the way the texts are produced and received by readers or audience and the last stage deals with the social impact of the texts.Without disregarding Fairclough’s three stages, this research only applies the first and the second stage in order to get deeper analysis. There are two problems approached in this research. The first is about the vocabulary choice of the text producer. For the first problem, the researcher concerns about the experiential, relational, expressive and metaphor values of the text. The second one is about the ideology constructed by the text producer. For the second problem, the researcher also semiotically presupposes the constructed ideology based on the character of each scene in the advertisement. This research uses qualitative method to analyze the data. The data are the oral, written and visual text in the advertisement. The data were collected from the transcription from the video of the advertisement.In conclusion, this research reveals how the political campaign advertisement of PDIP persuades the audience to choose Jokowi for the next president. It convinces the audience that Jokowi is a good social worker, part of Indonesian citizens who has the same dreams and hopes as Indonesian citizens’ and will sincerely work hard to make those dreams and hopes come true so that Indonesian citizens’ will have better future. Based on the presupposition of the characters in the advertisement scenes, the research also concludes that PDIP tries to gain support for the president election from the most influential social classes in Indonesia such academicians and workers. The researcher suggests the next researchers to conduct the same research in some other objects, such as speech and debate, and apply all stages in Fairclough’s Model of CDA.